# Math

posted by .

• Math -

So what is the question and I suspect you have a typo

• Math -

I always get confused working out this problem because I keep getting the wrong answer. cosine of x- sin squared x-1

• Math -

and it needs me to write the expression in factored form as an algebraic expression of a single trigonometric function.

• Math -

sin^2 x = 1 - cos^2 x

cos x - (1-cos^2 x) - 1

cos x - 2 + cos^2 x

cos^2 x + cos x - 2

as you wrote it

perhaps you mean

cos x - (sin^2 x -1)

cos x - (1 -cos^2 x - 1)

cos x + cos^2 x

cos x (cos x + 1)

• Math -

Where did you get the 1-cosine squared from?

• Math -

Find an algebraic expression equivalent to the given expression. sine (tan inverse of u/2)

• Math -

For the problem cosine of x-sine squared x-1 the choices are A)sine squared x, B) (cot x+1)(cot x-1), C) (cos x+2)(sin x-1), D)(sin x+2)(sin x-1)

• Math -

sin^2 x + cos^2 x = 1 identity
so
sin^2 x = 1 - cos^2 x

• Math -

(cos/sin +1)(cos/sin-1) = cos^2/sin^2 - 1

====================================
sin[ tan^-1(u/2) ]

right triangle
opposite = u

so hypotenuse = sqrt(u^2 +4)
so

sin = u/sqrt(u^2+4)

or [u sqrt (u^2+4)] / (u^2+4)

• Math -

Thank you for your help. Can you please delete all the questions I have typed in today?

## Similar Questions

1. ### Trigonometry.

( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated side …
2. ### Math - Pre- Clac

Prove that each of these equations is an identity. A) (1 + sinx + cos x)/(1 + sinx + cosx)=(1 + cosx)/sinx B) (1 + sinx + cosx)/(1 - sinx + cosx)= (1 + sin x)/cosx Please and thankyou!

Use the fundamental identities to simplify the expression. csc Q / sec Q so this would be 1/sinx / 1/cosx and then 1/sinx times cosx/1 = sin x cosx Is this correct so far?
4. ### Math 12

Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+cosx = cscxtanx/sinx+cosx Is the correct answer cscxtanx/sinx+cosx?
5. ### Trigonometry

Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+cosx = cscxtanx/sinx+cosx Is the correct answer cscxtanx/sinx+cosx?
6. ### Trigonometry Check

Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] = [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx] = [cosx-cosxsinx]/[cosx+cosxtanx] = [cosx(1-sinx]/[cosx(1+tanx] …
7. ### Precal

Verify the identity: sin^(1/2)x*cosx - sin^(5/2)*cosx = cos^3x sq root sin x I honestly have no clue how to approach the sin^(5/2)*cosx part of the equation
8. ### Trigonometry

Prove the following trigonometric identities. please give a detailed answer because I don't understand this at all. a. sin(x)tan(x)=cos(x)/cot^2 (x) b. (1+tanx)^2=sec^2 (x)+2tan(x) c. 1/sin(x) + 1/cos(x) = (cosx+sinx)(secx)(cscx) d. …
9. ### Precalculus/Trig

I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't know …
10. ### math

verify for sqrt(1-cosx)= sin/sqrt(1+cosx). I multiplied the right side by sqrt(1-cosx) and got sqrt(1-cosx)= sin*sqrt(1-cosx), but I don't know what to do with the sin.

More Similar Questions